Death Penalty for Apostasy: The Perspective of Hadith and Positive Law - Muhammadun Muhammadun; Oman Fathurrohman; Idris Ahmad Rifai (JURNAL INDO-ISLAMIKA, 2021)
This article analyses the death penalty for apostasy. Islam as moral and religious teaching recognizes the existence of such punishment. This can be traced from a number of verses from the Qur'an and the hadith of the Prophet which explain the concept of the death penalty aimed at certain criminal acts (jarimah) such as apostasy. However, is this the true understanding of the hadith to kill apostates? is still relevant to be applied in the present context, especially when the death penalty has received a very harsh response from human rights activists, both at national and international level? As a response to these questions, the writing analyzes the issue using a descriptive analysis method by making the hadith originating from Ibn Abbas as the research object and by using the theory of sunnah tasyri and ghairu tasyri' by Mahmud Syaltut. The comparison with positive law in Indonesia is also made at the end. In summary, the death penalty for apostasy is no longer relevant in the contemporary context. However, there is an exception when an apostate also commits rebellion (bughat) against the state.